Impact of Climate on Soil Wind Erosion in Karabakh Plain - Mammadova, Ulviyya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Soil wind erosion in the Karabakh Plain has become a critical environmental concern due to shifting climatic patterns and anthropogenic pressures. This study explores the influence of key climate variables, including wind intensity, rainfall, and temperature fluctuations, on soil erosion dynamics. The research identifies the most erosion-prone periods and regions by evaluating historical climate data and local soil properties. The analysis emphasizes the importance of vegetation cover, optimized land use, and adaptive practices in mitigating soil degradation. However, implementing these measures faces several obstacles, such as limited financial and technical resources, insufficient public awareness, and the intricate interaction between climate and soil systems. The study advocates for a multifaceted risk management approach integrating innovative agricultural techniques, active community participation, and supportive policy frameworks to enhance soil health and reduce erosion. The insights offered a foundation for developing targeted strategies to combat wind erosion and foster long-term environmental sustainability. Furthermore, the proposed measures are adaptable to similar challenges in other semi-arid areas, enabling a broader application of these solutions to enhance resilience against soil erosion.